К синонимии двух европейских видов мух-львинок (Stratiomyidae, Diptera) - Нарчук, Э.П. (Вестник зоологии, 1970)
On the basis of studying type-specimens from the collection of the Institute of Zoology of the Academy of Sciences of the Ukrainian SSR in Kiev and the Zoological ; Institute of the Academy of Sciences of the USSR in Leningrad the following new synonyms were established: 1.Oxycera ucrainica Paramonov, 1926 (Hermione) = Oxycera trilineata Fabric і u s, 1781; 2.Stratiomys winogradowinikitini P l e s к e, 1924 (Stratiomyia) = Stratiomys Chamaeleon Linnaeus, 1758. The type-specimen of Oxycera ucrainica Paramonov (Hermione) proved to be glued together of two specimens, the body belonging to the female of Oxycera trilineata L. and the head — to the female of Chloromyia formosa L.